2015
DOI: 10.3906/zoo-1402-9
|View full text |Cite
|
Sign up to set email alerts
|

Allometry of head size and shape dimorphism in the grass snake (Natrix natrix L.)

Abstract: Sexual dimorphism is a common phenomenon in the animal kingdom and has been reported in numerous snake species (see Shine, 1993 for review). In most colubrids (sensu lato) females are the larger sex (Shine, 1994). Body size differences are often accompanied by body shape and scalation differences, e.g., proportionally longer male tails or longer female trunks (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Surprisingly few studies on head shape evolution in snakes have been conducted despite the suggested relevance of head shape to diet in gape‐limited predators like snakes (Gans, ; Savitzky, ). Most studies exploring snake head shape have used linear descriptors in an attempt to explore growth allometries and sexual dimorphism (Arnold & Peterson, ; Vincent, Herrel & Irschick, ,b; Vincent & Herrel, ; Henao‐Duque & Ceballos, ; Borczyk, ) or to explore the role of head shape and head triangulation as a predator deterrent (Valkonen, Nokelainen & Mappes, ; Dalbosco et al ., ). Studies using geometric morphometrics are relatively rare and have mostly focused on head shape variation from a systematic perspective (Gentilli et al ., ; Mangiacotti et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly few studies on head shape evolution in snakes have been conducted despite the suggested relevance of head shape to diet in gape‐limited predators like snakes (Gans, ; Savitzky, ). Most studies exploring snake head shape have used linear descriptors in an attempt to explore growth allometries and sexual dimorphism (Arnold & Peterson, ; Vincent, Herrel & Irschick, ,b; Vincent & Herrel, ; Henao‐Duque & Ceballos, ; Borczyk, ) or to explore the role of head shape and head triangulation as a predator deterrent (Valkonen, Nokelainen & Mappes, ; Dalbosco et al ., ). Studies using geometric morphometrics are relatively rare and have mostly focused on head shape variation from a systematic perspective (Gentilli et al ., ; Mangiacotti et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Females grow larger in approximately two thirds of snake species studied so far and usually females possesses larger heads (Shine, 1993). These differences can be a result of a disproportional (allometric) head growth (Borczyk, 2015). However, this is not the case in A. eydouxi.…”
Section: Skull Size Dimorphismmentioning
confidence: 98%
“…Differences in head size and shape often result from selective pressure on dietary/ feeding niche separation, as they are usually accompanied by differences in average prey size, type, or both (e.g. Shine, 1986Shine, , 1991Shine, , 1993Houston & Shine, 1993;Forsman & Shine, 1997;Keogh, Branch & Shine, 2000;Shine et al, 2002;Gregory & Isaac, 2004;Vincent, Herrel & Irschick, 2004;Shine et al, 2012;Borczyk, 2015). The species in this study is one of the very few snake species that feed on fish eggs.…”
Section: Skull Size Dimorphismmentioning
confidence: 99%
See 2 more Smart Citations